2015
DOI: 10.18203/2319-2003.ijbcp20150038
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of Boswellia serrata for anxiolytic activity

Abstract: Anxiety disorders are the most common psychiatric disorders in the general population. Around 15-20% patients in general practice present with anxiety disorders. It is characterized by excessive worrying, apprehension, uneasiness and fear about uncertainties in future. Recent studies have shown that as many as 18% of Americans, 20.7% of Indians and 14% of Europeans are affected by anxiety. 1,2 The DSM-IV (American Psychiatric Association) covers the following major categories of anxiety disorders: panic disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It has been understood that 50 and 200mg/kg of B. serrata could ameliorate anxiety behaviors in Swiss albino mice in light and dark arena and elevated plus maze tests. (Adake et al, 2015). In a clinical trial oral administration of B. serrata reduced the intensity and frequency of headaches in patients with chronic cluster headaches (Lampl et al, 2012).…”
Section: Anti-anxiety and Anti-depressant Effectsmentioning
confidence: 99%
“…It has been understood that 50 and 200mg/kg of B. serrata could ameliorate anxiety behaviors in Swiss albino mice in light and dark arena and elevated plus maze tests. (Adake et al, 2015). In a clinical trial oral administration of B. serrata reduced the intensity and frequency of headaches in patients with chronic cluster headaches (Lampl et al, 2012).…”
Section: Anti-anxiety and Anti-depressant Effectsmentioning
confidence: 99%
“…Adake et al, reported the role of B. serrata in various psychiatric disorders, such as depression and anxiety in animal models, by modulating multiple neurotransmitter levels in the brain (117). Accordingly, AKBA showed anxiolytic activity in mouse models (118), and by reducing astrocyte activation and NF-κB activation, AKBA was able to revert an in vivo Aβ-associated depressive-like phenotype (119).…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Acute oral toxicity was done in male Swiss albino mice according to Organization of Economic Co-operation and Development (OECD) guidelines, ANNEX-423. [18] Animals were administered methanolic extract of Dolichos Biflorus seeds in a dose of 50,100, 200 and 2000mg/kg per orally to find out safe dose range in animals. Animals were observed for 48 hours from the time of drug administration.…”
Section: Acute Oral Toxicity Testmentioning
confidence: 99%